Entrepreneurship Menuju Agen Pastoral Yang Berkarakter Inovatif, Kreatif dan Mandiri - Hironimus Bandur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2013)
Enterpreneurship is well kown all over the world only because it reflects perfectly an autonomy and freedom of man. Enterpreneurhip has been socially defined as way of self-responsibility and theologically is defined as an expression of a human self-trencendence, and psychologically is realized as way of being smart in relation to the others very much linked to the basic human rights.The article is a lengthydiscource about man's creativity to deal with social and psychological, ecological, and political environment as part of being faithfull to God's mandate about their being in the world. There are five theological reflections about ENTREPRENEURSHIP:Enterpreneurship is a way of participating in God's work of creation; -Enterpreneurship is an expression of man's responsibility to the world according to God's mandate;-Enterpreneurhip is an expression of man's faith to God's presence; Enterpreneurship creates people around the world as “men of God", - Enterpreneurship is surely a divine vocation as "homo faber".